Safety profile of citrullus mucosospermus fursa fruit in wistar rats and characterization of its major toxic constituent (2019)
Citrullus mucosospermus Fursa known as 'Egusi baara' in Southwest Nigeria is a pale yellow green bitter fruit used ethnomedicinally for hyperlipidemia and weight gain management. There, however, exist few references to the safety profile of C. mucosospermus as it is known to contain toxic principles known as curcubitacins. Hence, this study evaluated the safety profile of C. mucosospermus, isolated and identified its major toxic curcubitacin constituent. The methanol extract of C. mucosospermus at graded doses of 100, 200, 400 and 1000 mg/kg body weight was administered orally to five groups of rats for 28 days including a control on a daily basis. The biochemical, histopathological and hematological indices were evaluated using standard procedures. The isolated compound was obtained from the purification of the ethyl acetate fraction of the fruit extract and the characterization was by spectroscopic (IR, NMR) procedures. An increase in neutrophil concentration after extract administration at a dose of 200 mg/kg was observed and a decrease in the liver enzymes at all doses tested confirming its hepatoprotective potential with mild to moderate changes observed in tissues of the kidney at 100 and 400 mg/kg and liver at all doses tested. The isolated compound was one of the toxic cucurbitacins identified as cucurbitacin E. The fruit pulp of C. mucosospermus could offer hepatoprotective effects despite its curcubitacin content.